2016
DOI: 10.1002/cphc.201600977
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulated Ionic Liquids for CO2 Capture: Using 1‐Butyl‐methylimidazolium Acetate for Quick and Reversible CO2 Chemical Absorption.

Abstract: The potential advantages of applying encapsulated ionic liquid (ENIL) to CO capture by chemical absorption with 1-butyl-3-methylimidazolium acetate [bmim][acetate] are evaluated. The [bmim][acetate]-ENIL is a particle material with solid appearance and 70 % w/w in ionic liquid (IL). The performance of this material as CO sorbent was evaluated by gravimetric and fixed-bed sorption experiments at different temperatures and CO partial pressures. ENIL maintains the favourable thermodynamic properties of the neat I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
76
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(88 citation statements)
references
References 84 publications
11
76
0
Order By: Relevance
“…The only exception was [P 4,4,4,4 ][Ac] that is solid at temperatures below 333 K. The encapsulation of IL not only enhances the mass transport properties but also lets us use ILs that would not reach the thermodynamic equilibrium under reasonable conditions due to the kinetic limitations . This improvement is due to the large increase of the contact surface area between the gas phase and the amino acid IL, upon dispersion of the absorbent in submicrodrops, in good agreement with previous results , , , ,…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The only exception was [P 4,4,4,4 ][Ac] that is solid at temperatures below 333 K. The encapsulation of IL not only enhances the mass transport properties but also lets us use ILs that would not reach the thermodynamic equilibrium under reasonable conditions due to the kinetic limitations . This improvement is due to the large increase of the contact surface area between the gas phase and the amino acid IL, upon dispersion of the absorbent in submicrodrops, in good agreement with previous results , , , ,…”
Section: Resultssupporting
confidence: 87%
“…The carbon submicrocapsules ( C c ap ) were synthesized following the template method described in detail in previous works , , , , , . A model of a silica sphere with a solid core and mesoporous shell were used as template.…”
Section: Methodsmentioning
confidence: 99%
“…This result is related to chemical absorption capacity of CO 2 by the IL [bmim][OAc]. In this case CO 2 reacts with the imidazolium ring cation forming carboxylate thus increasing CO 2 absorption capacity (Chen et al., 2011; Moya et al., 2016; Zareiekordshouli et al., 2018; Ziobrowski et al., 2016).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…% immobilized IL. Moya et al. (2016) used wet impregnation method to encapsulate IL in aluminum silicates.…”
Section: Introductionmentioning
confidence: 99%
“…with high specific surface area . The performance of ENIL materials was tested by different gas capture applications such as ammonia 31,44 and CO 2 in both physical 30,45 and chemical [46][47][48] absorption. These works concluded that the encapsulation of the IL does not decrease absorption capacities and increase very significantly the absorption rates, due to the strong increase of contact surface after IL encapsulation.…”
Section: Introductionmentioning
confidence: 99%